Upscaling green bond markets: the need for harmonised green bond standards - Kathrin Berensmann (Deutsches Institut für Entwicklungspolitik (DIE), 2017)
If a 2°C-compatible pathway is to be achieved, an enormous investment gap exists and this will need to be financed both with public and private funds. Green bonds have the potential to assume a crucial role in mobilising financial funds for the low-carbon transition. First, green bonds enhance the transparency on the underlying assets by disclosing the use of proceeds. Second, with long-dated maturities, they can match the long-term nature of issuer investment horizons with investor time horizons. Third, green bonds can augment issuers' reputation. Fourth, green bonds can attract a larger and more diversified investor group. This potential is reflected in the development of the green bond market. The annual issuance of labelled green bonds grew from USD 2.6 billion in 2012 to USD 82 billion in 2016 and in 2017 the Climate Bonds Initiative expect an increase to 150 USD billion. According to the Green Bond Principles (GBPs) – the most widely adopted international standard – green bonds are any type of bond instrument whose revenues are used to partly or completely finance or re-finance new and/or existing “eligible” green projects. While the green bond market has expanded sizably, one main problem in its further development is the lack of harmonised standards. Although several international and national taxonomies addressing green bond standards have improved practices around transparency, bonds structure and reporting (including the GBPs and the Climate Bonds Standard), there are no universal definitions of what constitutes a “green” bond. The architecture of green bond standards at the international and national level is fragmented. Several voluntary standards and various instruments for certifying green bonds have been established including second opinions, green ratings, and green bond indices. On the one hand, existing standards should be better harmonised at the international and national level because different standards reduce investor confidence and increase their transactions costs. In addition, the various certification schemes for green bonds, including second opinion-providers, should be aligned accordingly. To foster efficient trading and increase liquidity in the market, harmonisation of green bond indices and green bond listings rules should be increased. On the other hand, some diversity at national levels and across different types of green bonds is needed in view of country-specific circumstances and to take into account the different purposes of green bonds. Where diverse standards are required, however, transparency into their differentiation from accepted norms must be provided. In order to design harmonised standards, a vigorous dialogue among market participants is crucial. Annual consultation of the International Capital Market Association on the GBPs and the consultations organised by the Climate Bonds Initiative are important steps in the right direction. In the same vein, the current work of various authorities and private sector financial market actors on a “green bond term sheet” including standards for the definition, certification and validation of green bonds represents a crucial initiative. The G20 could promote harmonisation of green bond standards by providing an important dialogue platform for public and private financial actors. Country authorities of the G20 countries could take on a frontrunner role in supporting and implementing harmonised standards for green bonds. They should better align their different domestic standards amongst each other and align them with international standards.
Keywords: 330; Handel und Investitionen; Trade and investments